The new Portuguese language textbooks for the 7th grade and the (re)construction of grammar knowledge: Grammatical contents and (meta)linguistic operations - da Silva, António Carvalho (2017)
As of 2012/2013, the Portuguese Language textbooks were reviewed, following the implementation of Metas Curriculares de Português (Buescu et al., 2012), a new guideline that brought changes in discourse and practice of textbooks, at the level of contents, activities, that is to say, in the organization of grammatical knowledge.In fact, the guideline Metas Curriculares de Português defends: “The teaching of grammar should be carried out in close harmony with activities inherent to the achievement of the objectives of the other domains” (Buescu et al., 2012, p. 6). Such a view implies the trend of integrative grammar teaching, in which school knowledge is at the service of competences (both oral and written).In this context, while choosing for analysis the new textbooks for the 3rd cycle of Basic Education, the purpose of this paper is to verify the occurrence of new ways of approaching Grammar and evaluate if the issues related to this domain are considered as a (re)construction of school knowledge in the Portuguese language. It is, therefore, hoped that the conclusions of this study help illustrate the nature of school grammar, through the analysis of grammatical contents, activities and methods present in three Portuguese Language textbooks for the 7th grade.